Cybersnoops and mincing rascals. (Economist, 2014)
The article focuses on the U.S. Justice Dept.'s filing of thirty-one charges including identity theft and economic espionage against China's People's Liberation Army (PLA) on May 19, 2014. Topics include the international prosecution of cybercrime, the Chinese government's practice of spying on U.S. commercial activity, and the theft of trade secrets from American companies by Chinese spies.